Body image dissatisfaction, anthropometric and psychosocial characteristics in healthcare students from a university in south Brazil - Boclin, Karine de Lima Sírio; Farias, Julia Lima; da Cruz, João Paulo Bressan; Rigo, Lilian (Revista Contexto & Saúde, 2026)
Objectives: Body image can be described as a mental figure created on the body itself, influenced by the sum of all aspects that surround individuals throughout their lives. This study aimed to determine the prevalence of body image dissatisfaction and its possible link to anthropometric, demographic, and psychosocial characteristics in healthcare students at a university. Methods: The study has a cross-sectional design and involved 281 Medical and Dental school students. Body image satisfaction was assessed through the Body Shape Questionnaire (BSQ) and the Stunkard silhouette scale, classifying satisfaction or dissatisfaction. The exposure variables were sex, age, graduation course, self-perceived quality of life, satisfaction with health status, and Body Mass Index. Odds ratios were calculated through multivariate Logistic Regression models. Results: According to the instruments used, female medical students dissatisfied with their health status and being overweight present significantly greater chances of having body image dissatisfaction. Although the study population was largely formed by eutrophic or underweight individuals, many have shown to be dissatisfied, expressing the wish to reduce their body weight. Conclusions: Approximately 50% of the study population was satisfied with their body image, according to the BSQ, but only about 30% were satisfied according to the silhouette scale results. This study provides information that can aid preventive actions against health events associated with body image disorders.